TI_GERICHTE 52.2018.220 vom 28. März 2018 , Revoca della licenza di condurre a causa di inidoneità. Riammissione alla guida - TI Tribunale d'appello (2018)
Revoca della licenza di condurre a causa di inidoneità. Riammissione alla guida